Tire wear particles in the aquatic environment - A review on generation, analysis, occurrence, fate and effects. (1st August 2018) - Wagner, Stephan; Hüffer, Thorsten; Klöckner, Philipp; Wehrhahn, Maren; Hofmann, Thilo; Reemtsma, Thorsten
Abstract: Tire wear particles (TWP), generated from tire material during use on roads have gained increasing attention as part of organic particulate contaminants, such as microplastic, in aquatic environments. The available information on properties and generation of TWP, analytical techniques to determine TWP, emissions, occurrence and behavior and ecotoxicological effects of TWP are reviewed with a focus on surface water as a potential receptor. TWP emissions are traffic related and contribute 5–30% to non-exhaust emissions from traffic. The mass of TWP generated is estimated at 1, 327, 000 t/a for the European Union, 1, 120, 000 t/a for the United States and 133, 000 t/a for Germany. For Germany, this is equivalent to four times the amount of pesticides used. The mass of TWP ultimately entering the aquatic environment strongly depends on the extent of collection and treatment of road runoff, which is highly variable. For the German highways it is estimated that up to 11, 000 t/a of TWP reach surface waters. Data on TWP concentrations in the environment, including surface waters are fragmentary, which is also due to the lack of suitable analytical methods for their determination. Information on TWP properties such as density and size distribution are missing; this hampers assessing the fate of TWP in the aquatic environment. Effects in the aquatic environment may stem from TWP itself or from compounds released from TWP. It is concluded that reliable knowledge on transport mechanism to surface waters, concentrations in surface waters and sediments, effects of aging, environmental half-lives of TWP as well as effects on aquatic organisms are missing. These aspects need to be addressed to allow for the assessment of risk of TWP in an aquatic environment. Graphical abstract: Highlights: Knowledge on TWP emissions, fate, and effects in the aquatic environment is reviewed. Knowledge gaps regarding environmental relevance of TWP are identified. TWP emissions entering the aquatic environment are below 20% of the total TWP emissions. There is hardly any information about TWP effects at environmentally relevant concentrations.